A segurança pública e a criminalidade violenta em João Pessoa - Lima, João Batista de (2011)
This work examines the activities of the organs of the criminal prosecution system and the rates of homicide and crime against property in the city of João Pessoa in 2009. To put this theme in a wider panorama was performed a bibliographic research on crime and violence seeking to steer the study under the sociological point of view. It is presented an approach of the national public security system, in view of the constitutional principles, with the objective of facilitate the understanding of the role of each organ of that system in the State. To better situate the work it is designed a social profile of the city with the presentation of social indicators directly related to the public safety. It was made a detailed description of the operations of each of the members responsible for public security of the city, including police, prosecutors, judiciary system and penitentiary system, focusing in their systematic aspects. Through the presentation of historical series of data about police occurrences recorded in the city, it was made an analysis of the rates of homicide and crimes against property plotting the growth of these rates with the action of each of the organs of the security system.